2009
DOI: 10.1136/bjo.2009.161166
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity and specificity of photopic negative response of focal electoretinogram to detect glaucomatous eyes

Abstract: Focal PhNRs have diagnostic ability in detecting early glaucoma with high sensitivity and specificity, especially when the combined criterion is used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 16 publications
1
30
0
1
Order By: Relevance
“…12,15 PhNR is also selectively reduced in eyes with optic nerve atrophy, which is induced by trauma, compression, inflammation, ischemia, or gene mutation. [8][9][10] Our results provide additional evidence that focal macular PhNR is immediately and strongly attenuated by the onset of optic neuritis and that PhNR did not improve even after patients were treated with systemic corticosteroids, which resulted to improved visual acuity and visual field but not optic atrophy.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…12,15 PhNR is also selectively reduced in eyes with optic nerve atrophy, which is induced by trauma, compression, inflammation, ischemia, or gene mutation. [8][9][10] Our results provide additional evidence that focal macular PhNR is immediately and strongly attenuated by the onset of optic neuritis and that PhNR did not improve even after patients were treated with systemic corticosteroids, which resulted to improved visual acuity and visual field but not optic atrophy.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have used focal macular ERG to record the PhNR from localized retinal areas. [12][13][14][15] Machida et al 12,15 suggested that focal PhNR can detect early glaucoma with higher sensitivity and specificity than full-field PhNR. Therefore, the reduction of focal macular PhNR amplitude in patients with optic neuritis suggests that an inner retinal dysfunction of the macula already exists at the onset of symptoms.…”
Section: Reduction Of Focal Macular Erg In Patients With Optic Neuritismentioning
confidence: 99%
See 3 more Smart Citations